The Ongoing Journey of a Shigella Bioconjugate Vaccine - Martin, Patricia; Alaimo, Cristina (Vaccines (Basel), 2022)
Shigellosis is a serious disease with a major impact, especially in low-income countries where mortality and morbidity are high. In addition, shigellosis among travelers and military personnel is a cause of significant morbidity and contributes to the increase in antimicrobial resistance. The World Health Organization (WHO) considers the development of a Shigella vaccine a priority for public health. Over the past 60 years, several efforts to develop a Shigella vaccine have been pursued, without success. The principle of preventing shigellosis with a conjugate vaccine was demonstrated in the 1990′s, but this vaccine was not further developed. Bioconjugation is an innovative technology that allows the production of conjugate vaccines in a biological environment to preserve native immunogenic structures. In this review, we describe the journey of the bioconjugate Shigella vaccine, one of the most advanced clinical programs for a Shigella vaccine.